Peramalan Penerimaan Karyawan PT. Cipta Persada Infrastruktur Menggunakan Monte Carlo - Lasri Nijal; Roki Hardianto; Afenwil Rezky (ZONAsi: Jurnal Sistem Informasi, 2021)
Forecasting is done at PT. Cipta Persada Infrastructure (CPI) using the Monte Carlo method. The forecasting process refers to the use of employee recruitment data for the last 3 years (2018, 2019 and 2020). Currently the company is concentrating on toll road projects in Riau province including the Permai Toll Road, Pekanbaru – Bangkinang Toll Road and other toll roads in Riau. The simulation will be implemented using PHP programming. The results of this study are the level of prediction accuracy of employee acceptance at PT. Citra Persada Infrastructure using the Monte Carlo method is 80%. The Monte Carlo method is suitable to be used to accurately predict the level of employee acceptance for the following year, so that the results of the research can be used by PT. Citra Persada Infrastruktur (CPI) and other parties in need.